Advances in lipid methodology. - Christie, William W. (William Walker) (Woodhead Publishing in food science, technology, and nutrition., 2012)
This is the third volume of an occasional series of review volumes dealing with aspects of lipid methodology. As with the first two volumes, topics have been selected that have been developing rapidly in recent years and have some importance to lipid analysis. The authors are all leading international experts. Topics covered include: analysis of positional isomers of glycerolipids by non-enzymatic methods, separation of phospholipid classes by high-performance liquid chromatography, and nuclear magnetic resonance spectroscopy and lipid phase behaviour and lipid diffusion, among others.